One-Pot Microfluidics to Engineer Chitosan Nanoparticles Conjugated with Antimicrobial Peptides Using "Photoclick" Chemistry: Validation Using the Gastric Bacterium Helicobacter pylori - Fonseca, D R (2024)
Surface bioconjugation of antimicrobial peptides (AMP) onto nanoparticles (AMP-NP) is a complex, multistep, and time-consuming task. Herein, a microfluidic system for the one-pot production of AMP-NP was developed. Norbornene-modified chitosan was used for NP production (NorChit-NP), and thiolated-AMP was grafted on their surface via thiol-norbornene "photoclick" chemistry over exposure of two parallel UV LEDs. The MSI-78A was the AMP selected due to its high activity against a high priority (level 2) antibiotic-resistant gastric pathogen: Helicobacter pylori (H. pylori). AMP-NP (113 ± 43 nm; zeta potential 14.3 ± 7 mV) were stable in gastric settings without a cross-linker (up to 5 days in pH 1.2) and bactericidal against two highly pathogenic H. pylori strains (1011 NP/mL with 96 μg/mL MSI-78A). Eradication was faster for H. pylori 26695 (30 min) than for H. pylori J99 (24 h), which was explained by the lower minimum bactericidal concentration of soluble MSI-78A for H. pylori 26695 (32 μg/mL) than for H. pylori J99 (128 μg/mL). AMP-NP was bactericidal by inducing H. pylori cell membrane alterations, intracellular reorganization, generation of extracellular vesicles, and leakage of cytoplasmic contents (transmission electron microscopy). Moreover, NP were not cytotoxic against two gastric cell lines (AGS and MKN74, ATCC) at bactericidal concentrations. Overall, the designed microfluidic setup is a greener, simpler, and faster approach than the conventional methods to obtain AMP-NP. This technology can be further explored for the bioconjugation of other thiolated-compounds.